2021
DOI: 10.1108/apjml-04-2021-0233
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay for traditional ready-to-eat food packaging: examining the interplay between shape, font and slogan

Abstract: Purpose This paper investigates how to design traditional ready-to-eat food packaging by manipulating its shape, font and slogan to promote consumer buying intention and willingness to pay (WTP). Design/methodology/approach Two package designs, interplaying the square shapes (vertical vs horizontal), font formality (formal vs less formal/casual) and slogans (ethno-positioning vs short and catchy), were created and tested in an online experiment with 483… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…First, in terms of research perspective, this paper only explores the impact of different anchor characteristics on consumers’ willingness to pay at a premium, while the interaction of different types of anchors, anchor types and product types often also has different effects on consumer behavior ( 70 ). Second, although this paper focuses on the moderating role of limited-time limited-quantity, it does not make a strict distinction between such marketing stimuli ( 71 ). And although both limited-time or limited-quantity scarcity marketing stimuli can have an impact on consumers’ purchase intentions, there may be differences in the degree of impact between these two stimuli ( 72 ), future research could focus on this difference for a deeper exploration.…”
Section: Discussionmentioning
confidence: 99%
“…First, in terms of research perspective, this paper only explores the impact of different anchor characteristics on consumers’ willingness to pay at a premium, while the interaction of different types of anchors, anchor types and product types often also has different effects on consumer behavior ( 70 ). Second, although this paper focuses on the moderating role of limited-time limited-quantity, it does not make a strict distinction between such marketing stimuli ( 71 ). And although both limited-time or limited-quantity scarcity marketing stimuli can have an impact on consumers’ purchase intentions, there may be differences in the degree of impact between these two stimuli ( 72 ), future research could focus on this difference for a deeper exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Impressions of fun, playfulness and whimsy derived from seeing whimsically cute product packaging can direct the “first moment of truth” to a restricted set of external cues, despite the fact that the product is probably unknown to the consumer (e.g. Hanoch and Vitouch, 2004; Suci et al. , 2021; Gavilan and Fernández-Lores, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Impressions of fun, playfulness and whimsy derived from seeing whimsically cute product packaging can direct the "first moment of truth" to a restricted set of external cues, despite the fact that the product is probably unknown to the consumer (e.g. Hanoch and Vitouch, 2004;Suci et al, 2021;Gavilan and Fern andez-Lores, 2021). Therefore, it is relevant that consumers with low product familiarity rely more heavily on extrinsic cues when evaluating products (Seo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing amount of literature on RTE food in various regions, including a study on consumer buying intention toward RTE products in European, South American, African and Asian countries (Adeosun et al, 2023;Suci et al, 2022;Aviles et al, 2020;Tunung et al, 2019;Sgroi et al, 2018;Mandelkar, 2018). Most of the studies showed that the purchase intention of RTE food is primarily driven by price, quality, and convenience.…”
Section: Research Objectivementioning
confidence: 99%